Promoting Social Cohesion in Korea - Jones, Randall S.. (OECD Publishing, 2012)
Korea faces the challenge of reversing rising inequality while sustaining robust economic growth. Welltargeted increases in Korea's low level of social spending are needed to fill holes in the safety net, especially for the elderly. The development of social security depends on closing gaps in coverage, which are due in part to labour market dualism. Dualism creates serious equity concerns, as non-regular workers face significantly lower wages, precarious jobs, less coverage by social security and less training. A comprehensive approach is required to break down dualism, including reduced employment protection for regular workers, improved social insurance coverage for non-regular workers and expanded training of non-regular workers. Education reforms are also needed to promote inclusive growth, notably by: i) improving the access of low-income children to high-quality early childhood education and care; ii) reducing reliance on private tutoring, notably at hagwons; and iii) expanding income-contingent loans to tertiary students
Keywords: Social Issues/Migration/Health; Economics; Korea, Republic of